A novel 2-dimensional cosmic ray position detector based on a CsI（Na） pixel array and an ICCD camera - 葛永帅 王志刚 俞伯祥 谢宇广 章爱武 薛镇 刘颖彪 高龙 牛顺利 蔡啸 方建 孙希磊 吕绮雯 宁飞鹏 周莉 胡涛吗 吕军光 (中国物理C：英文版, 2012)
A novel 2-D cosmic ray position detector has been built and studied. It is integrated from a CsI（Na） crystal pixel array, an optical fiber array, an image intensifier and an ICCD camera. The 2-D positions of one cosmic ray track is determined by the location of a fired CsI（Na） pixel. The scintillation light of these 1.0× 1.0 mm CsI（Na） pixels is delivered to the image intensifier through fibers. The light information is recorded in the ICCD camera in the form of images, from which the 2-D positions can be reconstructed. The background noise and cosmic ray images have been studied. The study shows that the cosmic ray detection efficiency can reach up to 11.4%, while the false accept rate is less than 1%.